Differential expression of interleukin-32 in chronic rhinosinusitis with and without nasal polyps - Keswani, Anjeni (2011)
BACKGROUND: Chronic rhinosinusitis (CRS) is a heterogeneous disease characterized by local inflammation of the upper airways and sinuses and is frequently divided into polypoid CRS (CRSwNP) and non-polypoid CRS (CRSsNP). However, the mechanism of inflammation in CRS has still not been fully elucidated. The aim of the study was to investigate the role of IL-32, a recently discovered proinflammatory cytokine, in CRS. METHODS: We collected nasal epithelial cells and nasal tissue from patients with CRS and control subjects. We assayed mRNA for IL-32 by real-time PCR and measured IL-32 protein by ELISA, western blot and immunohistochemistry. RESULTS: The expression of mRNA for IL-32 was elevated in epithelial cells from uncinate tissue from patients with CRSsNP compared to patients with CRSwNP (p<0.05), control subjects (p=0.06) or epithelial cells from nasal polyp tissue (p<0.05). Production of IL-32 was induced by IFN-γ, TNF and dsRNA in primary airway epithelial cells. In whole tissue extracts, the expression of IL-32 protein was significantly elevated in patients with CRSwNP compared to patients with CRSsNP and control subjects. Immunohistochemistry data showed that IL-32 was detected in mucosal epithelial cells and inflammatory cells in the lamina propria. Levels of IL-32 were correlated with levels of CD3 and macrophage mannose receptor in nasal polyp tissue. Immunofluorescence data showed IL-32 co-localization with CD3 positive T cells and CD68 positive macrophages in nasal polyps. CONCLUSION: Overproduction of IL-32 may be involved in the pathogenesis of CRS, although the role of IL-32 in the inflammation in CRSsNP and CRSwNP may be different.